PROSPECTIVE VALIDATION OF A MODEL-BASED DOSING REGIMEN FOR AMIKACIN IN NEONATES: FEASIBLE AND RELEVANT. Issue 1 (14th December 2015) - Smits, Anne; Cock, Roosmarijn De; Allegaert, Karel; Vanhaesebrouck, Sophie; Danhof, Meindert; Knibbe, Catherijne
Abstract : Introduction: A neonatal amikacin dosing regimen was previously developed based on a population pharmacokinetic model. The aim of the current study was to prospectively validate this model-derived dosing regimen. Methods: First, early (before and after second dose) therapeutic drug monitoring (TDM) observations were evaluated for achieving target trough (<3 mg/L) and peak (>24 mg/L) levels. Secondly, observed concentrations were compared with model-predicted concentrations, whereby the results of an NPDE (normalized prediction distribution error) were considered as well. Subsequently, Monte Carlo simulations were performed. Finally, remaining causes limiting amikacin predictability (prescription errors and disease characteristics of outliers) were explored. Results: In 579 neonates [median (range) birth bodyweight 2285 (420–4850) g, postnatal age 2 (1–30) days, gestational age 34 (24–41) weeks], 90.5% of early peak levels reached 24 mg/L and 60.2% of trough levels was <3 mg/L (93.4% ≤5 mg/L). Observations were accurately predicted by the model without bias, which was confirmed by the NPDE. Monte Carlo simulations showed that peak concentrations >24 mg/L were reached in almost all patients. Trough values <3 mg/L were documented in 78–100% and 45–96% of simulated cases, respectively, when ibuprofen was co-administered or not. Suboptimal trough levels were found in patient subgroups with postnatal age <14 days and current weight >2000g. Conclusions: Prospective validation of a model-based neonatal amikacin dosing regimen resulted in optimized peak and trough concentrations in almost all patients. Adapted dosing for patients with suboptimal trough levels was proposed. Besides improving dosing individualization, feasibility and relevance of neonatal prospective validation studies was demonstrated.